2018
DOI: 10.1007/s00256-018-3042-1
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives in conventional and advanced imaging of the distal radioulnar joint dysfunction: review for the musculoskeletal radiologist

Abstract: Distal radioulnar joint (DRUJ) dysfunction is a common cause of ulnar sided wrist pain. Physical examination yields only subtle clues towards the underlying etiology. Thus, imaging is commonly obtained towards an improved characterization of DRUJ pathology, especially multimodality imaging, which is frequently resorted to arrive at an accurate diagnosis. With increasing use of advanced MRI and CT techniques, DRUJ imaging has become an important part of a musculoskeletal radiologist's practice. This article dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Bilateral CT evaluation of the DRUJs is useful for detecting differences in anatomical details and DRUJ congruency between normal and injured wrists 22,23 . There are various methods of quantifying the instability on axial CT images, such as the radioulnar line (or Mino's) method, the radioulnar ratio method, the subluxation ratio method, the epicenter method, and the congruency method 19,[24][25][26][27][28] . The radioulnar line method and the congruency method showed high false-positive rates 29 , while the epicenter method was the most speci c and reliable among them 28, 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral CT evaluation of the DRUJs is useful for detecting differences in anatomical details and DRUJ congruency between normal and injured wrists 22,23 . There are various methods of quantifying the instability on axial CT images, such as the radioulnar line (or Mino's) method, the radioulnar ratio method, the subluxation ratio method, the epicenter method, and the congruency method 19,[24][25][26][27][28] . The radioulnar line method and the congruency method showed high false-positive rates 29 , while the epicenter method was the most speci c and reliable among them 28, 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Several methods using imaging data have been reported to objectively evaluate DRUJ instability, including plain radiography, computerized tomography (CT), and ultrasound examination [20][21][22][23][24][25][26][27][28][29][30][31][32]. Nakamura et al reported that DRUJ subluxation and dislocation were indicated when the difference in the radioulnar distance between the affected and non-affected wrists was 6 mm or more on a normal lateral radiograph [20].…”
Section: Discussionmentioning
confidence: 99%
“…There are various methods of quantifying the instability on axial CT images, such as the radioulnar line (or Mino's) method, the radioulnar ratio method, the subluxation ratio method, the epicenter method, and the congruency method [21,[26][27][28][29][30]. The radioulnar line method and the congruency method showed high falsepositive rates [31], while the epicenter method was the most specific and reliable among them [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Variance appears decreased in supination and increased in either pronation or fist clenching. In chronic impaction, radiographs may show ulnocarpal osteoarthritis [206]. Before the development of osseous changes on radiographs and CT, MR demonstrates degeneration or tearing of the triangular fibrocartilage and lunotriquetral ligament [206].…”
Section: Ulnar Impaction Syndromementioning
confidence: 99%
“…In chronic impaction, radiographs may show ulnocarpal osteoarthritis [206]. Before the development of osseous changes on radiographs and CT, MR demonstrates degeneration or tearing of the triangular fibrocartilage and lunotriquetral ligament [206]. Associated MR findings include ulnocarpal chondromalacia, BME-like signal, and subchondral cyst-like change.…”
Section: Ulnar Impaction Syndromementioning
confidence: 99%